FACTORS AFFECTING GOING CONCERN AUDIT OPINION IN HOSPITALITY COMPANIES IN INDONESIA - Winarta, Wiwiek; Kuntadi, Cris (Universitas Pakuan, 2023)
ABSTRACTThis study aims to determine the factors influencing going concern audit opinion on the emphasis of the matter paragraph. The factors studied were 7 (seven) variables: size, growth, liquidity, solvability, asset turnover, working capital turnover, and company profitability. This study uses a quantitative research method using secondary data from hospitality companies in the consumer cyclical sector listed on the Indonesia Stock Exchange. The population of this research data uses 29 companies during the Covid-19 pandemic in 2020-2021. The purposive sampling technique resulted in 23 companies as samples. The number of observations was 46 companies for 2 (two) years. The data analysis method uses logistic regression. The data analysis result shows that only 1 (one) variable, namely the working capital turnover, significantly has a negative effect on the probability of getting going concern audit opinion on the emphasis of the matter paragraph. This study implies that working capital turnover is an early warning signal from the auditor in assessing the company's sustainability during the COVID-19 pandemic.ABSTRAKPenelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi opini audit going concern pada paragraf emphasis of matter. Faktor-faktor yang diteliti sebanyak 7 (tujuh) variabel, yaitu: ukuran, pertumbuhan, likuiditas, solvabilitas, perputaran aset, perputaran modal kerja, dan profitabilitas perusahaan. Metode penelitian dilakukan secara kuantitatif menggunakan data sekunder perusahaan perhotelan di sektor consumer cyclical yang terdaftar di Bursa Efek Indonesia. Populasi data penelitian ini sebanyak 29 perusahaan pada masa pandemi Covid-19 tahun 2020-2021. Teknik purposive sampling menghasilkan 23 perusahaan sebagai sampel dan jumlah amatan sebanyak 46 perusahaan selama 2 (dua) tahun. Metode analisis data menggunakan regresi logistik. Hasil analisis data menunjukkan bahwa hanya terdapat 1 (satu) variabel, yaitu perputaran modal kerja yang secara signifikan berpengaruh negatif terhadap peluang mendapatkan opini audit going concern pada paragraf emphasis of matter. Implikasi dari penelitian ini adalah perputaran modal kerja merupakan sinyal peringatan dini dari auditor dalam menilai keberlanjutan perusahaan pada masa pandemi COVID-19.